2021
DOI: 10.21203/rs.3.rs-717299/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification a ceRNA (XIST/miR-10a-5p/SERPINE1) Axis as a Prognostic Biomarker in Kidney Renal Clear Cell Carcinoma.

Abstract: Background: Kidney cancer is one of the most common malignancies, of which the most aggressive subtype was kidney renal clear cell carcinoma (KIRC), accounting for 80% of them. A growing number of studies point to the involvement of competitive endogenous RNAs in tumor development. However, the role of ceRNA network involved in KIRC remains unclear. Thus, the aim of this study was to investigate the BAP1-associated prognostic ceRNA in KIRC. Methods: We downloaded the RNAseq data from TCGA along with the releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…In addition, it has been shown that lncRNAs are involved in the immune process of the tumor microenvironment (TME) ( 80 ). For example, Liu et al ( 81 ) showed that a lncRNA XIST/miR-10a-5p/SERPINE1 axis mediated the TME of ccRCC. Immune cell infiltration analysis revealed that the lncRNA XIST can regulate the levels of CD4 + T cells, CD8 + T cells, macrophages, dendritic cells, neutrophils and other immune-related cells through the regulation of miR-10a-5p targeting SERPINE1 expression ( 81 ).…”
Section: Lncrnas and Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it has been shown that lncRNAs are involved in the immune process of the tumor microenvironment (TME) ( 80 ). For example, Liu et al ( 81 ) showed that a lncRNA XIST/miR-10a-5p/SERPINE1 axis mediated the TME of ccRCC. Immune cell infiltration analysis revealed that the lncRNA XIST can regulate the levels of CD4 + T cells, CD8 + T cells, macrophages, dendritic cells, neutrophils and other immune-related cells through the regulation of miR-10a-5p targeting SERPINE1 expression ( 81 ).…”
Section: Lncrnas and Cancermentioning
confidence: 99%
“…For example, Liu et al ( 81 ) showed that a lncRNA XIST/miR-10a-5p/SERPINE1 axis mediated the TME of ccRCC. Immune cell infiltration analysis revealed that the lncRNA XIST can regulate the levels of CD4 + T cells, CD8 + T cells, macrophages, dendritic cells, neutrophils and other immune-related cells through the regulation of miR-10a-5p targeting SERPINE1 expression ( 81 ). Another study showed that lncRNA NEAT1 similarly promoted the proliferation and migration of 786-O and ACHN kidney renal clear cell carcinoma (KIRC) cells by acting as a sponge of miR-10a-5p, thus indirectly activating SERPINE1.…”
Section: Lncrnas and Cancermentioning
confidence: 99%